Correlation between the presence of a self-splicing intron in the 25S rDNA of C.albicans and strains susceptibility to 5-fluorocytosine. - Mercure, S (1993)
Candida albicans presents a well characterized EcoRI RFLP pattern of intensely staining bands. One of these bands, the dimorphic 3.7/4.2 kbp fragment shown to originate from the ribosomal RNA-encoding regions (rDNA), has been used by several investigators to subdivide C. albicans strains in two distinct subtypes. In the present manuscript, we report that an epidemiological study of 120 C.albicans strains revealed a significant correlation between these subtypes and susceptibility to 5-fluorocytosine, an antifungal agent extensively used for biotyping C.albicans. The 4.2 kbp strains being generally more susceptible than their counterparts to this agent and one of its metabolic by-product, 5-fluorouracil. A 379 nucleotides insertion in the 25S rRNA-encoding gene of 4.2 kbp type strains was shown to be responsible for the 3.7/4.2 size difference. This intervening sequence is typical of a group I intron by its site of insertion, its predicted secondary structure, and its self-splicing capability. Assuming there is a genuine causal relationship between presence of the intron and resistance to 5-fluorocytosine, one possible mechanism suggests that inhibition of self-splicing by the insertion of 5-fluorouracil residues in the 25S rRNA precursor might be responsible for the higher susceptibility of 4.2 kbp type strains.